1996
DOI: 10.1007/bf02048269
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of relative risks of urinary stone formation after surgery for ulcerative colitis: Conventional ileostomy vs. J-pouch

Abstract: The risks of forming uric acid stones are high for both ileostomy and J-pouch patients, but our results suggest that there will be a reduction in calcium stone formation after J-pouch.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…Interestingly, in patients with short bowel syndrome post several resections for complicated Crohn’s, preservation of colon has been associated with higher incidence of renal stones compared with those who had a completion colectomy (24% vs 0% in a study of 52 patients)[10]. In a study of UC patients who had a panproctocolectomy, the risk of renal stone disease was compared between conventional ileostomy and ileal J-pouch; the risks of forming uric acid stones were high for both ileostomy and J-pouch patients, but J-pouch reduced the risk of renal stones containing calcium (the relative probability of calcium stone formation was 0.58 in ileostomy group vs 0.18 in the J pouch group)[11]. Another study on patients with ileal J-pouch post panproctocolectomy for UC showed that the presence of several extra-intestinal manifestations, no use of antibiotics and low serum bicarbonate level were the most important risk factors for the presence of concurrent urolithiasis; the overall incidence of the latter was 37% in this group[12].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, in patients with short bowel syndrome post several resections for complicated Crohn’s, preservation of colon has been associated with higher incidence of renal stones compared with those who had a completion colectomy (24% vs 0% in a study of 52 patients)[10]. In a study of UC patients who had a panproctocolectomy, the risk of renal stone disease was compared between conventional ileostomy and ileal J-pouch; the risks of forming uric acid stones were high for both ileostomy and J-pouch patients, but J-pouch reduced the risk of renal stones containing calcium (the relative probability of calcium stone formation was 0.58 in ileostomy group vs 0.18 in the J pouch group)[11]. Another study on patients with ileal J-pouch post panproctocolectomy for UC showed that the presence of several extra-intestinal manifestations, no use of antibiotics and low serum bicarbonate level were the most important risk factors for the presence of concurrent urolithiasis; the overall incidence of the latter was 37% in this group[12].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the risk of calcium containing stones also increases with ileostomy. In a retrospective study comparing IBD patients with ileostomy vs IBD patients with J-pouch vs controls, the relative risk of calcium containing stones formation was significantly higher (0.58 vs 0.18) in those with ileostomy[11]. …”
Section: Resultsmentioning
confidence: 99%
“…Recently, concerns have been raised that patients with an ileostomy are chronically dehydrated and have depleted calcium and magnesium stores, putting them at risk of renal impairment, renal stones and bone demineralisation. Due to the kidneys' attempt to conserve water and sodium, patients are also at greater risk of uric acid stones as a result of producing urine which is low in volume and pH, and with a high concentration of calcium and oxalate compared with healthy controls [27]. In addition, patients had 24-h urinary volume, calcium and magnesium concentrations significantly lower than controls, with 63% recording a urinary sodium excretion of less than 100 mmol/day.…”
Section: Dehydrationmentioning
confidence: 99%
“…Bile salt mal absorption in a dysfunctional terminal ileum (diseased or resected) results in fat mal absorption, that bind intraluminal calcium, decreasing the amount of calcium bound to oxalate (this last complex is poorly absorbed) resulting in increased oxalate absorption. Enteric hyperoxaluria is infrequent in patients with colectomy, ileostomy or jejunostomy, since the majority of oxalate is absorbed in the colon but can be met in parenteral nutrition, minimal oral intake, even in patients with colectomies [5,6]. A good strategy for preventing the recurrence of calcium oxalate stones includes hydration, oral urinary alkalization, low fat and oxalate diet, increasing the dietary intake of calcium and restricting the intake of salt.…”
mentioning
confidence: 99%